The impact of HIV/AIDS on education worldwide - Wiseman, Alexander W., 1968-; Glover, Ryan. (Bingley, U.K. : Emerald, 2012)
This volume of the International Perspectives on Education and Society series examines the relationship between HIV/AIDS and education worldwide. Much of the mystery surrounding HIV/AIDS and education lies in the fact that many factors contextualize their intersection. Many of the children who are at risk of not finishing school or have never had the chance to attend school live day-to-day in communities with high HIV/AIDS infection rates. To exacerbate the problem, in some countries the highest HIV/AIDS infection rates are in marginalized and extremely poor communities while in others it is within the most affluent communities. This volume examines how education supports, combats or reacts to HIV/AIDS awareness, prevention and impact worldwide as well as its impact on education systems and teaching forces. Given the context and prevalence of HIV/AIDS worldwide, this volume presents information, policy case studies, and empirical research for use by educators, policymakers, and organizations about the relationship between HIV/AIDS and education, including how HIV/AIDS has impacted education systems and the potential impact education has on HIV/AIDS.
HIV/AIDS and its impact on education in Sub-Saharan Africa : policy initiatives and challenges / Laban Ayiro -- HIV/AIDS education programs in Kenya : contexts of implementation in secondary schools in Kisii County / Kennedy Ongaga, Mary Ombonga -- HIV education in Ugandan secondary schools : attitudes of students, teachers, and administrators / W. James Jacob, Donald E. Morisky, Yusuf K. Nsubuga -- Multiple effects of education on disease : the intriguing case of HIV/AIDS in Sub-Saharan Africa / William Smith, Daniel Salinas, David P. Baker -- Taking a holistic approach to HIV/AIDS education in Zambian schools / Rosah Moonga Malambo -- HIV/AIDS and education in Botswana / Gaelebale Nnunu Tsheko -- The impact of HIV and AIDS on Lesotho primary school children / Grace Makeletso Ntaote -- Acting stubborn : understanding 'vulnerability' and secondary school participation in Lesotho / Anne Smiley -- Gender, sexuality and HIV and AIDS education in South Africa / Bhana Deevia, Singh Shakila -- Perceived factors underlying HIV risk behaviour of young people in South African schools / Maretha J. Visser -- 'New mutualism' in small (and micro) states : the AIDS generation and AIDS fatigue in the Caribbean educational policy space / Tavis D. Jules.
Includes indexes.
Print version record
Keywords: Health & Fitness -- Diseases -- AIDS & HIV; Health & Fitness -- Health Care Issues; Education -- General; Educational: Personal, social & health education (PSHE); Multicultural education; HIV-positive persons; Education -- Health aspects; HIV infections -- Social aspects